Respuesta :
a. [tex]x(t) = vt' = v(t+4) = 6(t+4) [m][/tex]
Let's call:
[tex]t[/tex] the time calculated from the moment Diane starts her motion and [tex]t'[/tex] the time calculated from the moment Derek starts his motion. Derek starts his motion 4 seconds before Diane: this means that has an "advantage" of 4 seconds, so we can write
[tex]t'=t+4[/tex]
Then:
[tex]v=6 m/s[/tex] is the uniform speed of Derek
Derek is moving in a uniform motion, so Derek's position will be given by (assuming that the starting position is zero):
[tex]x(t) = vt' = v(t+4) = 6(t+4) [m][/tex]
We see that this is correct: in fact, when t=0 (instant when Diane starts her motion), Derek has already travelled for
[tex]x(t=0)=v(0+4)=6 (4)=24 m[/tex]
b. [tex]x'(t)= \frac{1}{2}at^2 =\frac{1}{2}(2)t^2=t^2 [m][/tex]
t is the time calculated from the moment Diane starts her motion. Diane is moving by accelerated motion, with constant acceleration [tex]a=2 m/s^2[/tex] and initial velocity [tex]v_0=0[/tex], so its position at time t is given by the law of uniform accelerated motion:
[tex]x'(t)= \frac{1}{2}at^2 =\frac{1}{2}(2)t^2=t^2[/tex]
c. t = 8.74 s
The time t at which Diane catches up with Derek is the time t at which the positions of the two persons is equal:
[tex]x(t)=x'(t)[/tex]
By solving, we have:
[tex]6 (t+4) = t^2\\t^2 -6t -24 =0[/tex]
Which has two solutions:
t = -2.74 s --> negative, we can discarde it
t = 8.74 s --> this is our solution
d. 76.4 m
When Diane catches Derek, at t=8.74 s, she has covered the following distance:
[tex]x'(t=8.74s)=t^2 = (8.74 s)^2=76.4 m[/tex]
We can verify that Derek is at the same position:
[tex]x(t=8.74 s)=6(t+4)=6(8.74 +4)=76.4 m[/tex]